IMF Survey, Volume 35, Issue 20. (IMF Survey; IMF Survey ;, 2006)
Murilo Portugal, Agustin Carstens, Kyrgyz Republic, HIPC, central Asia, Indonesian debt, Saudi Arabian economy, Peter Kenen, European Central Bank, ECB, Danish economy, flexicurity,Burundi's economy, aid volatility, Indian and China, Doing Business.